Gamification and The Design of Badges in Relation to Educational Achievement. (September 2017) - Goodyear, Madison; Nathan-Roberts, Dan
Engaging students in learning has always been a difficult task for teachers. Gamification of education through badges is a new method for promoting student engagement that is quickly gaining popularity. For badges to effectively increase student engagement and reflect student learning, it is important to show different skills clearly, show the goals required to earn badges, have the ability to show the badges conveniently, and ensure that these badges can be used as valid representations of student skills. The literature reports that well-designed badges and badge systems promote self-regulated learning, increase quality of work, and provides multiple paths for education. Badges also were shown to promote teamwork, public displays of achievements, and provide more convenient but still valid ways of showing a student's complete skill set. However, more research is required to go further in-depth on the design of badge systems to maximize their potential to promote motivational learning.